Stress-Induced Spatial Memory Deficit Reversed by Basolateral Amygdala NMDA Receptor Inhibition in Male Wistar Rats - Rafia, Ahmad (Basic Clin Neurosci, 2020)
INTRODUCTION: The present study investigated the role of the Basolateral Amygdala (BLA) N-methyl-D-aspartate (NMDA) receptors in stress-induced spatial memory disturbance among the male Wistar rats. METHODS: The male Wistar rats (Average weight =200 g) were cannulated bilaterally in the BLA, and entered the study (n=6–8) after one week. They received seven electro–foot-shock stress sessions on seven consecutive days. Memantine (0.1, 1, and 5 μg/rat) or saline (0.5 μL/ rat) was injected into the BLA, five minutes before each stress session. The control groups received the same doses of memantine and no stress. After the end of the stress sessions, blood samples were taken from all animals to evaluate their plasma corticosterone. Also, the spatial learning and memory of the study animals were evaluated using the Barnes maze method. The animals experienced five consecutive days of training on the maze for spatial learning. On the sixth day, their spatial memory was evaluated on the maze. Time, distance, the number of errors, and the taking strategy for reaching the target hole were considered as the parameters for the spatial learning and memory evaluation. RESULTS: Stress increases the plasma corticosterone level, while memantine preadministration reduces the stress effects. Besides, stress increases the time and distance to the target hole and the number of errors. Stress changed the animals’ strategy from serial to random type. However, the intra-BLA memantine reversed all the disturbances induced by the stress. CONCLUSION: This study indicated that the BLA glutamate NMDA receptors modulate the effect of stress on spatial learning and memory deficit.